1/ ( x^2-5) (x+3) 2/(x+4) (x-x^2) 3/ (12x-5) (4x-1) 4/(3x-7) (1-16x)

Question

1/ ( x^2-5) (x+3)
2/(x+4) (x-x^2)
3/ (12x-5) (4x-1)
4/(3x-7) (1-16x)

in progress 0
Eva 4 tháng 2021-07-30T21:42:38+00:00 2 Answers 4 views 0

Answers ( )

    0
    2021-07-30T21:43:50+00:00

    1/ ( x²-5) (x+3)

    = x³+3x²-5x+15

    2/ (x+4) (x-x²)

    = x²-x³+4x-4x²

    = 2x²-x³+4x

    3/ (12x-5) (4x-1)

    = 48x²-12x-20x+5

    = 48x²-32x+5

    4/(3x-7) (1-16x)

    = 3x-18x²-7+112x

    = 115x-18x²-7

    0
    2021-07-30T21:44:03+00:00

    Đáp án:

     

    Giải thích các bước giải:

    $1/ (x^2-5)(x+3)$

    $=x^2(x+3)-5(x+3)$

    $=x^3+3x^2-5x-15$

    $2/ (x+4)(x-x^2)$

    $=x(x-x^2)+4(x-x^2)$

    $=x^2-x^3+4x-4x^2$

    $=4x-x^3-3x^2$

    $3/ (12x-5)(4x-1)$

    $=12x(4x-1)-5(4x-1)$

    $=48x^2-12x-20x+5$

    $=48x^2-32x+5$

    $4/ (3x-7)(1-16x)$

    $=3x(1-16x)-7(1-16x)$

    $=3x-48x^2-7+102x$

    $=105x-48x^2-7$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )